Sphingolipid metabolism and cell signaling. - Merrill, Alfred H.; Hannun, Yusuf A., 1955- (Methods in enzymology, 2000)
Sphingolipids are found in all eukaryotic and in some prokaryotic organisms and provide structure for cell membranes, lipoproteins, and other biological materials as well as participate in the regulation of cell growth, differentiation, and diverse cell functions, including cell-cell communication, cell-substratum interactions, and intracellular signal transduction. This volume presents methods used in studying enzymes of sphingolipid biosynthesis and turnover, including inhibitors of some of these enzymes, genetic approaches, and organic and enzymatic syntheses of sphingolipids and analogs. Its companion Volume 312 will contain information on analyzing sphingolipids, sphingolipid transport and trafficking, and sphingolipid-protein interactions and cellular targets. The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now with more than 300 volumes (all of them still in print), the series contains much material still relevant today--truly an essential publication for researchers in all fields of life sciences.